How economic freedom affects opportunity and necessity entrepreneurship in the OECD countries - Angulo-Guerrero, María José; Pérez-Moreno, Salvador Jesús; Abad-Guerrero, Isabel María (Elsevier, 2017)
This research addresses the extent to which economic freedom, understood as market economy-oriented institutions and policies, matters for opportunity entrepreneurship and necessity entrepreneurship. To this end, we carry out a panel data dynamic analysis in the OECD countries during the period 2001-2012 by using the system Generalized Method of Moments estimator. We examine the relationship between the Fraser Institute’s economic freedom index and its five areas, and both indicators from the Global Entrepreneurship Monitor on opportunity entrepreneurship and necessity entrepreneurship. We find that economic liberalization tends to encourage opportunity entrepreneurship and to discourage necessity entrepreneurship. In particular, opportunity entrepreneurship seems to benefit from improvements in legal structure and security of property rights and in regulation of credit, labor, and business, while both aspects and more freedom to trade internationally seem to damage necessity entrepreneurship.
Keywords: Organización de Cooperación y Desarrollo Económico; Economía de mercado; Economic freedom; Opportunity entrepreneurship; Necessity entrepreneurship; OECD countries